Implementation of Istishna and Salam Contract to Recca songkok Crafts - Muhammad Wahyuddin Abdullah; Nurul Faqiha Yasin (LAA MAISYIR: Jurnal Ekonomi Islam, 2020)
This study aims to determine the application of Islamic economic values in istishna and salam contract transactions for Songko Recca artisans. This study's focus only focuses on Islam's economic value between craftsmen and buyers of Recca songkok. This study uses a qualitative research paradigm with a phenomenological approach. Researchers took data by making observations, interview techniques, and documentation. Secondary data is obtained from literature reviews received from books, previous research, and websites that provide information about Islamic economic values. The data analysis method uses data reduction techniques, data presentation, concluding. The results of this study indicate that most of the craftsmen have applied Islamic economic values. This is shown starting at the contract or the ordering process until the goods are finished and ready to be shipped. The value of fairness and honesty applied by most craftsmen has a positive impact on their business. Besides, it will bring added value to crafters.